Time, fate and free will in the context of quantum theory - Polyanska, Viktoriya (Ukrainian Cultural Studies, 2024)
Background. The author tries to identify the connection between the phenomena of quantum physics and the philosophical concepts of "fate", "free will" and "time". By examining how the probabilistic nature of quantum mechanics challenges classical deterministic views, and bridging the gap between modern physics and age-old philosophical debates, the author seeks to offer a nuanced understanding of these fundamental concepts Methods. The investigation employs a multidisciplinary approach, incorporating scientific theories and discoveries alongside religious and philosophical perspectives. Various viewpoints and schools of thought are considered, spanning both Western scientific frameworks and Eastern philosophical traditions, to provide a comprehensive analysis of the topic. Results. The positions of total determinism and indeterminism are compared, highlighting their respective strengths and limitations. It delves into the parallels between Buddhist philosophy and contemporary quantum theory, suggesting that both share common ground in their understanding of reality. Additionally, the concept of creationism is examined within the context of quantum mechanics. Conclusions. The exploration reveals that the concepts of fate and free will, and their relationship with time, are deeply intertwined with the existence of a hidden quantum reality. This hidden reality, characterized by the inherent uncertainties and probabilistic nature of quantum mechanics, challenges the deterministic worldview upheld by classical physics. The investigation highlights that the interconnectedness of fate and free will with our understanding of time is profoundly influenced by the quantum realm, which introduces complexities such as the "measurement problem." As a result, the deterministic predictability of classical physics is replaced by a framework where probabilities and potentialities govern the behavior of particles. The study concludes that acknowledging the existence of this hidden quantum reality necessitates a re-evaluation of traditional notions of fate, free will, and time, suggesting that these concepts are more fluid and interconnected than previously thought. By bridging the gap between quantum theory and philosophical inquiry, the exploration offers new insights into the nature of reality and human agency, ultimately contributing to a more nuanced understanding of the universe and our place within it.